Brachial-ankle pulse wave velocity is associated with coronary calcium in young and middle-aged asymptomatic adults: The Kangbuk Samsung Health Study. Issue 2 (August 2015) - Cainzos-Achirica, Miguel; Rampal, Sanjay; Chang, Yoosoo; Ryu, Seungho; Zhang, Yiyi; Zhao, Di; Cho, Juhee; Choi, Yuni; Pastor-Barriuso, Roberto; Lim, So Yeon; Bruguera, Jordi; Elosua, Roberto; et al.
Abstract: Objective: To evaluate the association between brachial-ankle pulse wave velocity (baPWV), a convenient, non-radiating, readily available measurement of arterial stiffness, and coronary artery calcium (CAC), a reliable marker of coronary atherosclerosis, in a large sample of young and middle-aged asymptomatic adults; and to assess the incremental value of baPWV for detecting prevalent CAC beyond traditional risk factors. Methods: Cross-sectional study of 15, 185 asymptomatic Korean adults who voluntarily underwent a comprehensive health screening program including measurement of baPWV and CAC. BaPWV was measured using an oscillometric method with cuffs placed on both arms and ankles. CAC burden was assessed using a multi-detector CT scan and scored following Agatston's method. Results: The prevalence of CAC > 0 and CAC > 100 increased across baPWV quintiles. The multivariable-adjusted odds ratios (95% CI) for CAC > 0 comparing baPWV quintiles 2–5 versus quintile 1 were 1.06 (0.87–1.30), 1.24 (1.02–1.50), 1.39 (1.15–1.69) and 1.60 (1.31–1.96), respectively (P trend < 0.001). Similarly, the relative prevalence ratios for CAC > 100 were 1.30 (0.74–2.26), 1.59 (0.93–2.71), 1.74 (1.03–2.94) and 2.59 (1.54–4.36), respectively (P trend < 0.001). For CAC > 100, the area under the ROC curve for baPWV alone was 0.71 (0.68–0.74), and the addition of baPWV to traditional risk factors significantly improved the discrimination and calibration of models for detecting prevalent CAC > 0 and CAC > 100. Conclusions: BaPWV was independently associated with the presence and severity of CAC in a large sample of young and middle-aged asymptomatic adults. BaPWV may be a valuable tool for identifying apparently low-risk individuals with increased burden of coronary atherosclerosis. Highlights: BaPWV is a convenient measurement of arterial stiffness. In a large sample of young asymptomatic adults baPWV was robustly associated with CAC. This association remained significant after adjusting for potential confounders. BaPWV improved the ability of traditional risk factors for detecting prevalent CAC. BaPWV may be a valuable tool for detecting increased odds of subclinical coronary atherosclerosis.